MORPHOLOGICAL STRUCTURES OF MICROORGANISMS AND THE SYSTEMATICS OF PROKARYOTES: ORGANIZATIONAL STRUCTURE AND VIEWS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the morphological types of microorganisms, their shapes, structures, and functional significance in broad scope. The morphology of bacteria, fungi, viruses, archaea, and protozoa, their ecological adaptation, pathogenicity levels, and evolutionary importance are highlighted. The microscopic analysis methods and the role of morphological differences in diagnostics are discussed in detail. Microorganisms include bacteria, actinomycetes, yeasts, viruses, mold fungi, microscopic algae, and others. Microorganisms are divided into prokaryotes (organisms lacking a nucleus and chromosomal apparatus within the cell) and eukaryotes (organisms with a cytoplasm and a membrane-enclosed nucleus). For a long time, all prokaryotes were classified into a single domain (the largest taxonomic group). However, research by microbiologist Carl Woese in the 1970s demonstrated that prokaryotes are divided into two distinct lineages: Bacteria and Archaea. Currently, these groups are considered to constitute two of the three domains of life. The third domain (Eukarya) includes all eukaryotes such as plants, animals, and fungi.